Entrepreneurship Training in Home-Scale Jamu Production to Support Land Intensification and Agroindustry Development - Norbertus Citra Irawan; Dewi Rahmawati Intan Permatasari; Mahananto; Wahyu Hidayat; Adhisty Puri Damayanti; Ermareta Hanasya Rachman (Universitas Tunas Pembangunan Surakarta, 2026)
Entrepreneurship training in home-scale herbal drink (jamu) production is an effort to enhance students’ competencies in business diversification and downstream processing of spice-based products. This activity was motivated by the low level of students’ knowledge and skills in utilizing oil palm plantation land for additional commodities and their limited ability to process agricultural products into value-added goods. This community service activity aimed to improve students’ knowledge, motivation, and entrepreneurial interest through jamu production training. The activity was conducted using an interactive lecture method by inviting a jamu MSME entrepreneur as the resource person and involved 50 students of the oil palm education program. The evaluation was carried out using pre- and post-training questionnaires and participant observation. The results showed an average increase of 44% in participants’ understanding of spice crop potential, jamu production processes, business opportunities, and entrepreneurial interest. In addition, 84% of participants expressed interest in independently producing jamu and 78% were interested in developing a jamu business. The activity also increased participants’ awareness of optimizing land use and developing agro-industry-based businesses. These findings indicate that practitioner-based training is effective in improving students’ entrepreneurial capacity and has strong potential to support the development of new sustainable herbal-based enterprises.